Innovative tool for sustainable production and recycling of agro-industrial wastes - Turchanin Oleg S.; Grigoryan David R.; Ukraintseva Irina V.; Nazarov Igor V.; Tolstoukhova Tatiana N. (BIO Web of Conferences)
This article explores the potential of using black lionfly larvae in the entomoindustry as an alternative to traditional animal husbandry. Traditional methods of food production are resource intensive and lead to environmental pollution. The use of insects, in particular black lionfly larvae, to process organic waste into valuable products such as fodder, biohumus and protein concentrates is a sustainable and environmentally friendly approach. Experiments have shown that the larvae efficiently recycle different types of waste, and less water and feed are required to produce 1kg of protein from the insects compared to beef protein production. The developed business model of the entomotechnology enterprise includes centralised and decentralised logistics and offers three options for business development. The most promising is a mixed approach, combining the production and sale of equipment and final products. It is noted that the market for entomoindustry equipment is underdeveloped, indicating potential for development. The study emphasises the economic and environmental feasibility of using black lionwort for sustainable production.